2017
DOI: 10.1292/jvms.17-0148
|View full text |Cite
|
Sign up to set email alerts
|

Operative techniques of percutaneous endoscopic mini-hemilaminectomy using a uniportal approach in dogs

Abstract: The present study aimed to investigate the technical feasibility of percutaneous endoscopic mini-hemilaminectomy via a uniportal approach, and to evaluate the possibility of decompression and endoscopic examination of the thoracic and lumbar spinal canals in small dogs during such procedures. Fresh canine cadavers of mixed-breed dogs (n=7) were used in this study. Following injection of a barium and agarose mixture (BA-gel) to stimulate intervertebral disc herniation, percutaneous endoscopic mini-hemilaminecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 23 publications
(41 reference statements)
1
20
1
Order By: Relevance
“…We concluded that the minimally invasive intramuscular approach through a 2‐cm channel offered adequate access to the target area, with the tendinous attachment onto the articular process as the sole structure being cut. These findings support the reports of MISS cadaveric study on the feasibility of the techniques.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We concluded that the minimally invasive intramuscular approach through a 2‐cm channel offered adequate access to the target area, with the tendinous attachment onto the articular process as the sole structure being cut. These findings support the reports of MISS cadaveric study on the feasibility of the techniques.…”
Section: Discussionsupporting
confidence: 90%
“…Surgical loupes are popular among neurosurgeons but offer only limited magnification. The use of exoscopes and endoscopes has been reported in a few veterinary reports . Video‐assisted ventral slots have been used in cadavers and in clinically affected dogs, whereas mostly cadaveric studies have been reported for the thoracolumbar and lumbosacral region, with only one report of using an endoscope in a study in live dogs .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Standard approaches to the spine, so called open techniques , involve muscle dissection from the bony elements with removal of ligaments, tendons, and bony structures, which are all important parts of the dorsal stabilizing element of the spine . Because of the frequency of spinal surgery in dogs, interest in MISS has been growing . However, most studies are limited to dog cadavers; only two reports have described MISS thoracolumbar technique in live dogs .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, today's surgical trends point toward reducing the invasiveness of all surgeries. Minimally invasive surgery of the spine is now performed routinely in humans and has also been reported clinically and experimentally for the cervical and thoracolumbar regions in dogs . These studies rely either on percutaneous palpation or fluoroscopy to target the correct intervertebral disc space.…”
Section: Introductionmentioning
confidence: 99%